Problems and Prospects in Survey Research. (March 2016) - Moy, Patricia; Murphy, Joe
Over the last few decades, survey research has witnessed a number of developments that have affected the quality of data that emerge using this methodology. Using the total survey error (TSE) approach as a point of departure, this article documents chronic challenges to data quality. With the aim of facilitating assessments of data quality, this article then turns to best practices in the disclosure of survey findings based on probability and nonprobability samples. Finally, (p)reviewing the use of technology and social media, it provides an overview of the opportunities and challenges for survey research today.